Decreasing unnecessary utilization in acute bronchiolitis care: Results from the value in inpatient pediatrics network. Issue 1 (9th October 2012) - Ralston, Shawn; Garber, Matthew; Narang, Steve; Shen, Mark; Pate, Brian; Pope, John; Lossius, Michele; Croland, Trina; Bennett, Jeff; Jewell, Jennifer; Krugman, Scott; Robbins, Elizabeth; et al.
Abstract BACKGROUND: Acute viral bronchiolitis is the most common diagnosis resulting in hospital admission in pediatrics. Utilization of non–evidence‐based therapies and testing remains common despite a large volume of evidence to guide quality improvement efforts. OBJECTIVE: Our objective was to reduce utilization of unnecessary therapies in the inpatient care of bronchiolitis across a diverse network of clinical sites. METHODS: We formed a voluntary quality improvement collaborative of pediatric hospitalists for the purpose of benchmarking the use of bronchodilators, steroids, chest radiography, chest physiotherapy, and viral testing in bronchiolitis using hospital administrative data. We shared resources within the network, including protocols, scores, order sets, and key bibliographies, and established group norms for decreasing utilization. RESULTS: Aggregate data on 11, 568 hospitalizations for bronchiolitis from 17 centers was analyzed for this report. The network was organized in 2008. By 2010, we saw a 46% reduction in overall volume of bronchodilators used, a 3.4 dose per patient absolute decrease in utilization (95% confidence interval [CI] 1.4–5.8). Overall exposure to any dose of bronchodilator decreased by 12 percentage points as well (95% CI 5%–25%). There was also a statistically significant decline in chest physiotherapy usage, but not for steroids, chest radiography, or viral testing. CONCLUSIONS: Benchmarking within a voluntary pediatric hospitalist collaborative facilitated decreased utilization of bronchodilators and chest physiotherapy in bronchiolitis. Journal of Hospital Medicine 2013. © 2012 Society of Hospital Medicine